Language as symbolic action : essays on life, literature, and method - Burke, Kenneth, 1897-1993 (University of California Press, 1966)
From the Preface:The title for this collection was the title of a course in literary criticism that I gave for many years at Bennington College. And much of the material presented here was used in that course. The title should serve well to convey the gist of these various pieces. For all of them are explicitly concerned with the attempt to define and track down the implications of the term ";symbolic action,"; and to show how the marvels of literature and language look when considered form that point of view.